SUSTAINABLE LIGNIN EXTRACTED FROM BANANA STEM BIOMASS AS A FUNCTIONAL UV-BLOCKING INGREDIENT IN SUNSCREEN - Sheryl Ayesha; Nanda Aurelia Salsabila S; Teguh Pambudi; Hasti Asfarina; Hilman Imadul Umam; Fajar Amelia Rachmawati Putri (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Banana stem biomass, an abundant agricultural by-product, contains significant lignin content and offers strong potential for valorization through green extraction technologies. In this study, lignin was extracted using an environmentally friendly Deep Eutectic Solvent (DES) composed of choline chloride and citric acid and subsequently incorporated into sunscreen cream formulations at concentrations of 2%, 3%, and 4%. The photoprotective performance of the formulations was evaluated through UV–Vis spectrophotometry, while pH measurements ensured compliance with SNI 16-4399-1996. FTIR analysis was conducted to compare the structural characteristics of DES-extracted lignin with those obtained using conventional NaOH extraction. The results revealed that all lignin-based formulations effectively absorbed UVA (320–400 nm) and UVB (280–320 nm) radiation, with UV absorbance increasing alongside lignin concentration; the 4% formulation showed the strongest UV-blocking capability. All samples maintained a skin-compatible pH of approximately 6. FTIR spectra further indicated that DES-extracted lignin preserved aromatic structures more effectively than NaOH-extracted lignin. Overall, the findings highlight the potential of banana stem-derived lignin as a natural UV-blocking and antioxidant ingredient for eco-friendly sunscreen products, supporting the advancement of sustainable cosmetic innovation.